(untitled) (Malaysian Journal of Civil Engineering, 2018)
In this paper, a numerical modification is carried out on the Layer Equation Method (LEM) of El Gendy and Herrmann to be applicable for analyzing 1-D consolidation of soft clay subjected to cyclic loading. The LEM is applicable for multilayered soil system subjected to variable initial stress along depth. The proposed solution is used for normally and over consolidated clays subjected to different types of cyclic loading considering the basis of the method of Toufigh and Ouria. The LEM is incorporated by the authors into the geotechnical software ELPLA and is verified with two verifications. The results of the verifications are close to the references results. The proposed solution is applied for circular storage tanks as a structure subjected to cyclic loading from filling and discharging cycles. An application was held to study the effect of cyclic loading on two zones located at Port-Said city in Egypt using real soil data from real sites. The results of the average degree of consolidation and consolidation settlement versus time are presented for both zones.